Phosphatidylethanolamine aggravates Angiotensin II-induced atrial fibrosis by triggering ferroptosis in mice - Huang, Fangze; Liu, Ximao; Liu, Junjie; Xie, Yu; Zhao, Li; Liu, Deshen; Zeng, Zifeng; Liu, Xiu; Zheng, Shaoyi; Xiao, Zezhou (Frontiers in Pharmacology, 2023)
As atrial fibrosis is the main feature of atrial structural remodeling, inhibiting atrial fibrosis is crucial to the prevention of atrial fibrillation (AF) progression. Research has shown the correlation between abnormal lipid metabolism and AF progression. However, the effect of specific lipids on atrial fibrosis remains unclear. In the present study, we applied ultra-high-performance lipidomics to analyze the lipid profiles in patients with AF and identify phosphatidylethanolamine (PE) as the differential lipid associated with AF. To detect the effect of the differential lipid on atrial fibrosis, we performed the intraperitoneal injection of Angiotensin II (Ang II) to mice to induce atrial fibrosis and supplemented PE in diets. We also treated atrial cells with PE to evaluate the cellular effect of PE. We found that PE supplementation aggravated atrial fibrosis and increased the expression of the fibrosis-related protein in vitro and in vivo. Moreover, We detected the effect of PE on the atrium. We found that PE increased oxidation products and regulated the expression of ferroptosis-related proteins, which could be alleviated by a ferroptosis inhibitor. PE increased peroxidation and mitochondrial damage in vitro, which promoted cardiomyocyte death induced by Ang II. Examination of protein expression in cardiomyocytes indicated that PE triggered ferroptosis and caused cell death to participate in myocardium fibrosis. In summary, our findings demonstrated the differential lipid profiles of AF patients and revealed the potential effect of PE on atrial remodeling, suggesting that inhibition of PE and ferroptosis might serve as a potential therapy to prevent AF progression.